Solitary fibrous tumors of the pleura: A single center experience at National Cancer Center, China. Issue 12 (10th November 2018) - Tan, Fengwei; Wang, Yalong; Gao, Shugeng; Xue, Qi; Mu, Juwei; Mao, Yousheng; Gao, Yushun; Zhao, Jun; Wang, Dali; Zhou, Lina; He, Jie
Abstract : Background: This study explored the clinicopathological features, predictive factors of malignancy, effectiveness of video assisted thoracic surgery (VATS), and prognosis of solitary fibrous tumor of the pleura (SFTP). Methods: A single‐center retrospective study of the data of 82 patients with SFTP who were surgically treated in our department between January 2003 and December 2015 was conducted. Results: A total of 82 SFTPs (70 benign, 12 malignant) were included and all patients underwent complete en bloc resection. SFTPs originated from the visceral pleura in 47 (57%) and the parietal pleura in 35 (43%) patients. In our cohort, malignant tumors were often symptomatically large, and the patients with malignant SFTPs (mSFTPs) often had a family history of neoplasms. Patients in the VATS group ( n = 22) had tumors with significantly smaller diameters, required a shorter surgical duration and shorter hospital stay, and experienced less intraoperative blood loss and less postoperative chest tube drainage compared to the thoracotomy group ( n = 60). No tumor recurrence was found in benign SFTP (bSFTP) patients. The long term survival and disease‐free survival rates of mSFTP patients were 76% and 53%, respectively. Conclusion: Larger tumor diameter and a family history of neoplasm may be predictive factors for mSFTP; however, this conclusion needs to be verified in large cohort. VATS is safe and reliable for treating selected SFTP patients. Local recurrence is associated with mSFTP patient death, thus close follow‐up of such patients is crucial.